The Effect of Loving-Kindness Meditation and Self-Confidence on the Learning Outcomes of Students at SMA Negeri 1 Tanjung, North Lombok - Sulan Sulan; Mettadewi Wong; Pratama Eka Putra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study was motivated by the low learning outcomes of students at SMA Negeri 1 Tanjung, North Lombok, which became a major concern, particularly because many students experience academic anxiety and low self-confidence that hinder active participation and understanding of Buddhist Religious Education material. Initial observations revealed that students were reluctant to express opinions, easily distracted, and lacked focus during lessons. Loving-Kindness Meditation (Metta Bhavana) has been implemented at the school to enhance mental calmness and concentration; however, its effectiveness has not yet been empirically validated. Therefore, this study was conducted with the aim of examining the influence of Loving-Kindness Meditation and self-confidence, both individually and simultaneously, on students’ learning outcomes in Buddhist Religious Education, with the intention of providing empirical evidence regarding the role of spiritual and psychological aspects in supporting academic achievement. This study employed a quantitative method using numerical data to measure the influence of Loving-Kindness Meditation and self-confidence on learning outcomes. Data collection techniques were carried out through questionnaires, documentation, and limited observation. The questionnaires were distributed to 100 Buddhist students at SMA Negeri 1 Tanjung as research respondents, who were selected using purposive sampling. Documentation was used to obtain supporting data related to students’ learning outcomes, while limited observation was conducted to examine the initial learning conditions and students’ behavior during the learning process. All data were then objectively analyzed using SmartPLS through the statistical technique of Structural Equation Modeling (SEM) to assess the relationships between variables, including the simultaneous effect of Loving-Kindness Meditation and self-confidence on students’ learning outcomes. The results of this study indicate that Loving-Kindness Meditation (X1) has a positive and significant effect on students’ learning outcomes (Y), and self-confidence (X2) also has a positive and significant influence. Furthermore, simultaneous analysis shows that both variables together significantly affect students’ learning outcomes. Therefore, these two variables play an important role in enhancing the quality of learning.